CREATION OF ROAD PLANS FOR VARIOUS TERRAINS USING THE MODERN CREDO SOFTWARE COMPLEX - Farrukh Madiev; Saidova Navruza (American Journals Publishing, 2024)
At present, in the design and construction of settlements, industrial enterprises, transport communications, canals and other structures, along with traditional design methods (analytical, graphic, model-graphic, layout-graphic), automated design systems based on the use of digital terrain models (DTM) are increasingly used. It is the DTM that is the source material for the operation of computer-aided design systems (CAD) for construction and automated control systems (ACS). The use of DTM significantly simplifies and accelerates many processes of urban management, from calculating areas to compiling lists of tax defaulters.
Keywords: Beijing cabbage, cabbage head, warehouse, temperature, relative humidity of air, refrigeration compartment, cooling Ridge, paper, parchment paper, polyethylene (stretch), natural reduction, corrosion, commodity product.